Technology As A Modern Arabic Language Learning Medium - Kurnia Wahyuni; Habiburrahman; Mugni Assapari; Satriawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The role of technology is massive across various fields, including the learning of Arabic. This study aimed to explore the role of technology as a catalyst in transforming Arabic language learning patterns. The research fell under the category of library research with a descriptive qualitative approach. The focus of the study was on analyzing research journals that discuss the use of technology in Arabic language learning. The results showed that the role of technology in contemporary Arabic language learning (21st century) through various media such as artificial intelligence, applications, different digital platforms, and social media had a positive impact on the ease of access to communication, facilitating learning, delivering material, and providing evaluations in the context of digital learning. Technology played a crucial role in the success of learning and overcoming the barriers of distance, space, and time. Technology had given rise to many media such as animated videos, podcasts, cognitive game applications, and learning based on virtual reality and augmented reality, contributing to enriching students' understanding of Arabic language skills. The use of technology as a learning medium had become a daily necessity in the present day.